Anxiety and Defense Mechanism Analysis in Jenny Han’s To All The Boys I’ve Loved Before - Alya Nurul Izzaty; Sulistya Ningtyas (Universitas Negeri Surabaya, 2026)
This study aims to examine how conflicts trigger anxiety in Lara Jean, the main character of Jenny Han’s To All the Boys I’ve Loved Before, and how her defense mechanisms emerge to protect her from threats that make her feel uncomfortable. A psychoanalytical approach based on Freud’s theory was applied. This study revealed that Lara Jean experiences three types of anxiety: realistic, neurotic, and moral anxiety. To cope with this anxiety, she uses more specific defense mechanisms, including projection, denial, and displacement. Lara Jean, as a girl who has never been in a love relationship with anyone, experiences a conflict resulting in anxiety within her love relationships. However, Lara Jean uses a defense mechanism that shifts from a form of protection to character development that marks her emotional maturity.